2021
DOI: 10.3390/medicina57111258
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–Fetal Outcomes in Women with Endometriosis and Shared Pathogenic Mechanisms

Abstract: The connection between endometriosis and pregnancy outcomes is trending among the research topics. Until recently, endometriosis and its painful symptomatology were considered to be alleviated by pregnancy. However, these beliefs have shifted, as emerging literature has demonstrated the role of this condition in affecting pregnancy evolution. The underlying pathogenesis of endometriosis is still poorly understood, all the more when pregnancy complications are involved. Debatable opinions on endometriosis assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 98 publications
2
7
0
Order By: Relevance
“…According to an Italian study, women with endometriosis are twice as likely to have a preterm delivery. The current study's findings are consistent with the prior research that revealed a link between endometriosis and placenta previa [ 30 ]. However, it is worth noting that the interaction between adverse pregnancy outcomes, such as placenta previa, and hypertensive disorders in pregnancy increases the risk of cesarean delivery and fetal growth restriction and may compromise the accuracy of the association between endometriosis and adverse pregnancy outcomes [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…According to an Italian study, women with endometriosis are twice as likely to have a preterm delivery. The current study's findings are consistent with the prior research that revealed a link between endometriosis and placenta previa [ 30 ]. However, it is worth noting that the interaction between adverse pregnancy outcomes, such as placenta previa, and hypertensive disorders in pregnancy increases the risk of cesarean delivery and fetal growth restriction and may compromise the accuracy of the association between endometriosis and adverse pregnancy outcomes [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Endometriosis exerts a significant social and psychological burden on women in many respects, including quality of life, intimacy, childbearing, education and work, and emotional health ( 26 ). Furthermore, endometriosis is often related to cardiovascular and autoimmune diseases ( 27 ). Recent advances in the field of endometriosis have identified novel biomarkers that may be developed as targets for the treatment of endometriosis, including immunomodulators and inhibitors, which have been tested on animal models ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a higher frequency of placenta previa has been reported in the adenomyosis group. By altering the uterine environment through anatomical, functional and immunochemical mechanisms, adenomyosis has been proposed as a contributing factor in the pathophysiological link between endometriosis and abnormal placentation [ 9 , 29 , 30 , 31 , 32 , 33 , 34 ]. Both endometriosis and adenomyosis may disfigure the endometrial cavity and this might concur to the inefficient function of the uterus at the time of delivery.…”
Section: Discussionmentioning
confidence: 99%